2022
DOI: 10.1002/1873-3468.14474
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the regulation of cellular catabolic metabolism in macrophages through nuclear receptors

Abstract: Regulation of cellular catabolic metabolism in immune cells has recently become a major concept for resolution of inflammation. Nuclear receptors (NRs), including peroxisome proliferator activator receptors, 1,25‐dihydroxyvitamin D (3) receptor, liver X receptors, glucocorticoid receptors, oestrogen‐related receptor α and nuclear receptor 4A1, have been identified as major modulators of inflammation, affecting innate immune cells, such as macrophages. Evidence emerges on how NRs regulate cellular metabolism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…GCs are also highly anti-inflammatory, especially for macrophage function through classical but also metabolic pathways [25][26][27] , and therefore may be involved in the inflammatory response during obesity. We propose that GCs potentially have a dual role during obesity- (1) suppressing inflammatory activation of macrophages in adipose tissue, and (2) promoting lipid accumulation and insulin resistance by acting on adipocytes.…”
mentioning
confidence: 99%
“…GCs are also highly anti-inflammatory, especially for macrophage function through classical but also metabolic pathways [25][26][27] , and therefore may be involved in the inflammatory response during obesity. We propose that GCs potentially have a dual role during obesity- (1) suppressing inflammatory activation of macrophages in adipose tissue, and (2) promoting lipid accumulation and insulin resistance by acting on adipocytes.…”
mentioning
confidence: 99%
“…However, some immune aspects in PPARα have been studied in different cell types and systems. Study of PPARα global knockout (KO) mice, which have an increase in cytokine expression in some instances, has suggested an anti-inflammatory role for this protein ( 26 , 27 ). In another study, PPARα-KO mice showed increased helper CD4 + T cell type 17 (Th17) generation resulting in increased pathology of murine experimental autoimmune encephalomyelitis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…During efferocytosis, there is activation of a molecular switch that drives phenotype and bioenergetics changes in macrophages from M1 (high glycolytic activity) towards M2 (oxidative phosphorylation) to resolve inflammation. The exact mechanism of this phenotype switch is still unclear but is thought to involve the activity of various specialized pro-resolving lipid mediators (SPMs) (such as eicosanoids, lipoxins, resolvins, protectins, maresins) (Ryan & Godson 2010, Börgeson & Godson 2012 and nuclear receptor signalling (PPARγ/α, liver X receptors, glucocorticoid receptors, orphan nuclear receptors (Nur)) (Stifel et al 2022). During this process, lysosomal degradation of apoptotic bodies through catabolism of cell corpses furthermore provides substrates for the metabolic switch to favour oxidative phosphorylation and triggers various nuclear transcription factors to induce the transcription of immunosuppressive cytokines such as IL10 and transforming growth factor-β (Zhang et al 2019b).…”
Section: Monocytes/macrophagesmentioning
confidence: 99%